Biomechanical Comparison of Anterograde and Retrograde Lesser Trochanter Avulsion Repair. Issue 1 (20th January 2020) - Otto, Alexander; Baldino, Joshua B.; DiCosmo, Alyssa M.; Coyner, Katherine; Johnson, Jeremiah D.; Obopilwe, Elifho; Cote, Mark P.; Muench, Lukas N.; Beitzel, Knut; Scheiderer, Bastian; Imhoff, Andreas B.; Mazzocca, Augustus D.; et al.
Background: Lesser trochanter avulsions are rare injuries in adolescents. Severe cases with relevant fragment displacement can be treated surgically. However, no standard approach is available in the literature. Operative techniques are presently limited to anterograde fixations. A new retrograde approach to reduce operative difficulty and postoperative morbidity has been proposed. So far, no biomechanical comparison of these techniques is available. Hypothesis: Retrograde repair of the lesser trochanter with a titanium cortical button will produce superior stability under load to failure and similar displacement under cyclic loading compared with anterograde fixation with titanium suture anchors. Study Design: Controlled laboratory study. Methods: Sixteen paired hemipelvic cadaveric specimens (mean age, 62.5 ± 10.7 years) were dissected to isolate the lesser trochanter and iliopsoas muscle. After repair of a simulated lesser trochanter avulsion, specimens were tested under cyclic loading between 10 and 125 N at 1 Hz for 1500 cycles before finally being loaded to failure at a rate of 120 mm/min in a material testing machine. Motion tracking was used to assess displacement at the superior and inferior aspects of the iliopsoas tendon under cyclic loading. Results: Load to failure was significantly greater for the retrograde repair compared with the anterograde repair (1075.24 ± 179.39 vs 321.85 ± 62.45 N; P = .012). Mean displacement at the superior repair aspect (retrograde vs anterograde: 3.29 ± 1.84 vs 4.39 ± 4.50 mm; P = .779) and mean displacement at the inferior aspect (3.54 ± 2.13 vs 4.22 ± 4.48 mm; P = .779) of the iliopsoas tendon did not significantly differ by the type of repair. Mode of failure was tendon tearing by the sutures for each retrograde repair and anchor pullout for each anterograde repair. Conclusion: Surgical repair of lesser trochanter avulsion fractures with retrograde fixation using a titanium cortical button demonstrated superior load to failure and similar displacement under cyclic loading compared with anterograde fixation using suture anchors. Clinical Relevance: The retrograde approach provides a biomechanically validated alternative to other surgical techniques for this injury.